5 - Employment Practices within the Minibus Taxi Industry in Johannesburg: A Study of Precariousness of Jobs in South Africa - Siyabulela C. Fobosi (African Sociological Review, 2019)
Following the work of Standing (2011), Clarke (2006) and others, I use the precariat theory to define the existence of precarious working conditions within the minibus taxi industry. I use precariousness to describe how the employment practices in the industry, labour legislation from the Department of Labour (DoL), regulations and public transport policies by the Department of Transport (DoT) define the nature of the industry. This article is situated in the broader context of my PhD thesis which investigated the impact of the Taxi Recapitalisation Programme (TRP) on precarious working conditions within the minibus taxi industry in Johannesburg. Using qualitative research methods, I conducted a total of fifty – eight interviews for my thesis. Results revealed the existence of precarious working `conditions within the minibus taxi industry – in the Global South. The article contributes to the study of precarity in the Global South, similar to Clarke (2006) who examined precarious work in post – apartheid South Africa. The minibus taxi industry’s labour conditions place its drivers in a position of precarity. This means that taxi drivers are daily exposed to bad working conditions which are not in line with the Basic Conditions of Employment Act (BCEA) or the Sectoral Determination (SD) on wages.